Antagonistic activity of Trichoderma spp. Against Fusarium oxysporum dan Fusarium solani Causes Yellow Disease in Pepper (Piper Nigrum Linn) - Resti Provilia; Rahmad Lingga; Tri Wahyuni (International Journal of Ecophysiology, 2023)
Bangka Belitung is a pepper producing area known as the Muntok White Pepper. One of the main challenge in the cultivation of pepper is attackingof pathogens. The decrease in pepper is caused by yellow disease due to the attack of the fungus Fusarium solani and Fusarium oxysporum. The control of yellow disease is carried out using biological agent such asTrichoderma spp. This study aimed to obtain local isolates of Trichoderma spp. from the pepper garden in CengkongAbang Village as a biological agent and to measure the inhibition of Trichoderma spp. on the growth of Fusarium oxysporumandFusarium solani in vitro. The research methods used were the isolation, identification and antagonism of Trichoderma spp. against Fusarium oxysporumand Fusarium solani. The result of isolation soil samples from the healthy pepper rhizosphere and yellow diseased pepper obtained 74 isolates of Trichoderma spp. The identification of 74 isolates obtained 7 types of Trichoderma spp. encoded THA, THB, THC, THD, THE, THF, THG. Fungal antagonist test of Trichoderma spp. against Fusarium oxysporum produced the highest percentage of inhibition in THB2Mb and THB2La isolates of 7.13% and 7.1%, while the highest percentage of inhibition from Trichoderma sp. against Fusarium solani was obtained in THD1Ib and TSD2Mb isolates at 7.33% and 7.23%